2010
DOI: 10.1002/j.0022-0337.2010.74.12.tb05011.x
|View full text |Cite
|
Sign up to set email alerts
|

Augmented Kinematic Feedback from Haptic Virtual Reality for Dental Skill Acquisition

Abstract: We have developed a haptic virtual reality system for dental skill training. In this study we examined several kinds of kinematic information about the movement provided by the system supplement knowledge of results (KR) in dental skill acquisition. The kinematic variables examined involved force utilization (F) and mirror view (M). This created three experimental conditions that received augmented kinematic feedback (F, M, FM) and one control condition that did not (KR-only). Thirty-two dental students were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 18 publications
(21 reference statements)
1
29
0
1
Order By: Relevance
“…Research has shown that a VR simulation facility alongside an experienced instructor providing real-time feedback is the most productive method of teaching in a simulation environment. It improves students' hand-eye coordination, fine motor skills and reflection skills and becomes especially effective in the very early stages of skill acquisition leading to a conservative preparation approach and better skill retention [84][85][86]. Thus, it can be proposed that VR simulation technology is a useful supplementary tool to conventional dental training approaches, and its effective and safe use possibly with some modifications to allow distance learning can be considered during COVID-19 pandemic.…”
Section: The Role Of Simulation In Dental Educationmentioning
confidence: 99%
“…Research has shown that a VR simulation facility alongside an experienced instructor providing real-time feedback is the most productive method of teaching in a simulation environment. It improves students' hand-eye coordination, fine motor skills and reflection skills and becomes especially effective in the very early stages of skill acquisition leading to a conservative preparation approach and better skill retention [84][85][86]. Thus, it can be proposed that VR simulation technology is a useful supplementary tool to conventional dental training approaches, and its effective and safe use possibly with some modifications to allow distance learning can be considered during COVID-19 pandemic.…”
Section: The Role Of Simulation In Dental Educationmentioning
confidence: 99%
“…Additionally, learners with low visual‐spatial ability seem to benefit more from simulation training than conventional training . The role of feedback in dental pre‐clinical training has also been investigated in conventional , computer‐assisted and VR environments . In conventional pre‐clinical operative training (phantom head simulators), the effect of providing continuous concurrent feedback from an instructor has been found to result in significant performance improvements relative to presentation of terminal KR feedback alone .…”
Section: Introductionmentioning
confidence: 99%
“…The most distinguishing feature of haptic simulators (Simodont ® ) is the science of creating a sense of real touch in a virtual environment to allow the user to realistically 'feel' what they are working on. 9 It was introduced by Moog (Nieuw-Vennep, the Netherlands) and named as Simodont ® Dental Trainer (Figure 1). The device teaches the user to drill in a representative and virtual manner.…”
mentioning
confidence: 99%